2016
DOI: 10.5812/pedinfect.29985
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of Clinical Manifestations and Laboratory Findings in Neonatal Sepsis

Abstract: Background: Neonatal sepsis is one of the major causes of morbidity and mortality in newborns. Since early diagnosis of neonatal septicemia is important for timely initiation of correct antimicrobial therapy and considering the existence of variability in nonspecific clinical laboratories, we assessed the role of clinical manifestations and laboratory findings to find the right diagnosis. Objectives: The aim of this study was to evaluate, record and rank the clinical manifestations and lab data of neonates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
4
10
0
Order By: Relevance
“…Although clinical manifestations were frequently subtle and nonspecific, they can be helpful in the early detection of NIs. Respiratory distress, poor feeding, and fever were the most common presentations of NIs in neonates, which was in line with other studies (21,22). In our study, 58.3% of the neonates had positive cultures.…”
Section: Discussionsupporting
confidence: 93%
“…Although clinical manifestations were frequently subtle and nonspecific, they can be helpful in the early detection of NIs. Respiratory distress, poor feeding, and fever were the most common presentations of NIs in neonates, which was in line with other studies (21,22). In our study, 58.3% of the neonates had positive cultures.…”
Section: Discussionsupporting
confidence: 93%
“…The change in mean platelet counts after adjustment may be attributed to the effect of the confounding factors (volume of blood transfusion, sepsis and presence of bronchopulmonary dysplasia) on ROP [ 24 , 25 , 26 , 27 ]. Sepsis is commonly known to be related to thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis not only causes endothelial damage with resultant increased platelet activation, initiating a vicious cycle of subsequent platelet-mediated cytotoxic endothelium damage [ 28 ], but also causes bone marrow suppression, with consequent decreased platelet production [ 29 ]. A meta-analysis investigating the association between sepsis and ROP found that sepsis increases the risk of ROP [ 26 ]. This is consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that the most frequent symptoms of NS were refusal to suck (43.5%), lethargy (30.9%), respiratory distress (21.1%), hypothermia (14.3%), fever (9.4%) ( Table 2). The clinical presentation slightly varied between studies in that the study done by Masoumeh Hematyar et al [6] showed respiratory distress in (44.5%), jaundice in (25.5%), vomiting in (23.6%) and poor feeding in (20.9%), lethargy (10.9%), fever (3.6%), seizure (1.8%), & in another study by Mohsen M. Shalaby et al [7] the most common clinical features of neonatal sepsis were poor suckling (87.5%), respiratory distress (82.5%) and lethargy (77.5%). Among the laboratory investigations for sepsis screening, the total WBC count, Absolute Neutrophil Count (ANC), and Creactive protein (CRP) showed statistically significant increase in group A and B than group C. On comparison of MPV among the three groups, a statistically significant increase in MPV was found in group A and B (cut off 10 fl) than group C (P <0.001).…”
Section: Discussionmentioning
confidence: 99%